Disclosure and Competition for Capital - Cheng, Stephanie F.; Cuny, Christine; Xue, Hao (Management Science, 2023)
Ownership segmentation in the municipal bond market gives rise to competition among local issuers for a limited supply of capital. We consider the disclosure implications of this competition for capital, using Moody’s 2010 recalibration of the municipal rating scale. The recalibration placed lowly upgraded issuers at a disadvantage relative to their highly upgraded peers within the same market segment. We develop a model in which two municipal bond issuers compete for investors’ capital by choosing bond yields. The model predicts the issuer that is disadvantaged by the recalibration is more likely to improve its disclosure to better compete with its advantaged peer if (i) the rating upgrade that its peer receives is higher and (ii) competition for capital is fiercer. Empirically, we find that the disadvantaged issuers provide more and timelier financial disclosures after the recalibration. This improvement in disclosure quality increases in the extent of the issuer’s disadvantage, arises only if we consider peers with whom the issuer directly competes for capital, and is pronounced when the local capital supply is constrained. Our analytical and empirical analyses support the idea that a competitive disadvantage in raising capital in segmented markets can motivate issuers to improve disclosure quality. This paper was accepted by Brian Bushee, accounting. Supplemental Material: The data files are available at https://doi.org/10.1287/mnsc.2022.4525 .